ANALISIS DAMPAK PERUBAHAN KEBIJAKAN PEMERINTAH TERHADAP EKONOMI RUMAHTANGGA PETANI SAYURAN DI KOTA PEKANBARU - Nurjalilah Nurjalilah; Djaimi Bakce; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2020)
The purpose of this study was to analyze the impact of government policy changes on aspects of production, allocation of working time, income and households expenditure of vegetable farmer in Pekanbaru City. The econometric approach of simultaneous equations with the Two Stage Least Squares method is used to answer the purpose of the study. The main findings of this research are: Firstly, simulation of increase of vegetable price have a positive impact to household economic decision of farmer. Secondly, the simulation of the decline in fertilizer prices also has a positive impact on the households economic decision of farmer. Thirdly, the simulation of increased wages of labor negatively impacts the economic decisions of farm households. Fourthly, the policy of increasing vegetable prices has a greater impact on household economic decision making than the policy of fertilizer price reduction. The policy implications that governments can take to increase household incomes are by increasing vegetable prices and maintaining the stability of input prices. Extension activities on appropriate harvest and post harvest handling techniques and the expansion of the target market can increase the price of the commodity produced so that the impact on the increase in households income of farmer.